Country‐of‐birth differences in adverse health behaviours among people with type 2 diabetes - Seyed Morteza Shamshirgaran; Louisa Jorm; Hilary Bambrick; Annemarie Hennessy (Australian and New Zealand Journal of Public Health, 2015)
Abstract Objective: To identify differences in patterns of adverse health behaviours among people with type 2 diabetes according to country or region of birth. Methods: Population‐based study of 23,112 individuals with type 2 diabetes aged 45 years and older, from New South Wales, Australia. Self‐reported questionnaire data and logistic regression models were used to estimate odds ratios for adverse health behaviours according to country or region of birth, adjusted for confounding factors. Results: People with diabetes born in the Middle East and in the United Kingdom (UK) were more likely to be current smokers than those born in Australian, while those from Asia were less likely to be smokers. Relative to Australian‐born people with diabetes, those born in the Middle East were more likely to have insufficient physical activity, while those born in Oceania, North West Europe and the UK were less likely. People with diabetes from Asia, North Africa, the Middle East and Sub‐Saharan Africa were less likely to consume alcohol than those born in Australia, but people born in the UK were slightly more likely to consume alcohol. People with diabetes born in the UK, Asia, and North Africa were more likely than those born in Australia to have an inadequate intake of fruit and vegetables. Conclusion: Adverse health behaviours among people with type 2 diabetes varied markedly according to country or region of birth. Promoting smoking cessation and increasing physical activity levels among people with diabetes who were born in Middle Eastern countries are clear priorities.